Personality traits, pain perception, and patient attitudes toward orthodontic treatment with fixed appliances - Monika Lorek; Anna Jarząbek; Magdalena Sycińska-Dziarnowska; Sylwia Gołąb; Ewa Cichocka; Gianrico Spagnuolo; Gianrico Spagnuolo; Krzysztof Woźniak; Liliana Szyszka-Sommerfeld; Liliana Szyszka-Sommerfeld (Frontiers in Neurology)
BackgroundOrthodontic pain is defined as orofacial pain induced by orthodontic tooth movement. The application of orthodontic forces activates periodontal sensory receptors, resulting in a cascade of nociceptive pain processing and transduction in both the central and peripheral nervous systems, which is eventually felt by patients. The purpose of this study was to evaluate the association between pain perception, pressure pain threshold (PPT), attitude toward orthodontic treatment, and personality traits in adolescents treated with fixed orthodontic appliances.MethodsThe study involved 60 subjects aged 16 to 18 year-olds divided into 2 groups: group 1 consisted of 30 patients undergoing orthodontic treatment with fixed orthodontic appliances, and group 2 consisted of 30 untreated subjects. The tool for data collection was a questionnaire that assessed pain experience for treated subjects, pain expectation for untreated subjects, and attitude toward treatment using a visual analog scale (VAS) marked at 10-mm intervals. The assessment of patients’ personality profiles was carried out using the NEO Five-Factor Inventory (NEO-FFI). PPT was measured using a digital force algometer. The results were subjected to statistical analysis. The significance threshold was established at p < 0.05.ResultsThe multivariate analysis showed that treatment status was the only variable affecting patients’ average attitude scores and average pain experience/expectation scores measured using a VAS, and average PPT scores (p < 0.0001). Gender and personality traits did not affect PPT scores, pain intensity, and attitude toward treatment (p > 0.05). The results of the follow-up univariate analysis demonstrated a significant difference in the patients’ average attitude toward treatment (p = 0.017) and PPT scores (p < 0.0001) between the treated and untreated groups.ConclusionOrthodontic treatment may impact the pressure pain thresholds measured using algometry and patient attitudes toward treatment. This knowledge is essential for orthodontists and patients, as the success of orthodontic treatment largely depends on the patient’s cooperation and motivation, which may be affected by patient’s attitude toward treatment and pain perception. This, in turn, encourages the search for effective methods of pain reduction during orthodontic treatment and attention to communication between orthodontists and patients for a good understanding of the procedures used.